2014
DOI: 10.4306/jknpa.2014.53.4.221
|View full text |Cite
|
Sign up to set email alerts
|

Korean Addiction Treatment Guidelines (III) : Psychosocial Treatment of Alcohol Use Disorder

Abstract: ObjectivesZZThe aim of this study is to develop guidelines for psychosocial treatment of alcohol use disorder. MethodsZZAccording to the ADAPTE manual, the Korean alcohol use disorder treatment guidelines were developed by the guideline development committee. Recommendations from foreign guidelines were evaluated regarding the applicability and acceptability to domestic circumstances. In addition, a survey from experts was conducted, along with a review of Korean literature. By these means, recommendations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
1
0
3
Order By: Relevance
“…이 외에도 음주운전, 폭행, 방화, 주취 상태에서의 범죄 등 지 역사회에 이차적인 피해를 유발한다 [5]. 이와 같이 알코올 사용 장애는 개인의 문제를 넘어서 가족과 사회 전반에 부정적인 영향 을 끼치는 질병으로 치료가 중요하다 [6,7].…”
Section: 서 론 연구의 필요성unclassified
See 2 more Smart Citations
“…이 외에도 음주운전, 폭행, 방화, 주취 상태에서의 범죄 등 지 역사회에 이차적인 피해를 유발한다 [5]. 이와 같이 알코올 사용 장애는 개인의 문제를 넘어서 가족과 사회 전반에 부정적인 영향 을 끼치는 질병으로 치료가 중요하다 [6,7].…”
Section: 서 론 연구의 필요성unclassified
“…알코올 사용 장애 환자를 위한 치료에는 금단 치료와 재발 예 방 치료, 약물치료와 심리 사회적 치료 등으로 다각적인 관리가 제공되고 있다 [7]. 특히 알코올 사용 장애 환자에게 있는 정신건 강 문제를 치료하기 위해 다양한 심리 사회적 중재가 제공되었다 [8][9][10][11].…”
Section: 서 론 연구의 필요성unclassified
See 1 more Smart Citation
“…In Korea, therapeutic approaches such as pharmacological therapy, self-help groups, social skill training, and cognitive restructuring have also been used ( Joo, 2009 ), and reports have been published on the effectiveness of motivational counseling and cognitive therapy (S. K. Lee, 2019 ). However, in Korea, AUD has low service utilization and treatment rates (B. H. Lee et al, 2013 ; Oh et al, 2014 ), high relapse rates ( Seo et al, 2010 ), and high outpatient treatment cessation rates (S. K. Lee, 2019 ). In addition, a 12-month follow-up study of people with alcohol dependence or alcohol abuse conducted in the United States found that 61% of men and 63% of women reported at least one recurrence ( Zywiak et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%